2016
DOI: 10.1177/0023677216658916
|View full text |Cite
|
Sign up to set email alerts
|

Caecum location in laboratory rats and mice: an anatomical and radiological study

Abstract: Intraperitoneal (i.p.) injection is the most frequently used method for implementing parenteral therapies in rats and mice. Whether the caecum is located in the right caudal quadrant or left caudal quadrant in the abdominal cavity is not clear. For that reason, we have developed a method for identifying the location of the caecum in rats and mice and thus revealed the most reliable location for i.p. injection in these animals. Two hundred Wistar albino rats and 100 BALB/c mice were used. The location of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Unfortunately, it appears that misinjections are always possible, in part due to the variable location of the cecum. [6, 14, 15, 21]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it appears that misinjections are always possible, in part due to the variable location of the cecum. [6, 14, 15, 21]…”
Section: Discussionmentioning
confidence: 99%
“…This dose was selected from previous work demonstrating benefits in terms of a faster death and reduced variability of effects. [6, 14, 15, 21]…”
Section: Discussionmentioning
confidence: 99%
“…Secara umum, jumlah BAL pada isi sekum lebih tinggi dibandingkan pada feses akhir intervensi (Tabel 2). Hal ini karena sekum merupakan bagian awal kolon yang menjadi tempat fermentasi serat oleh mikroba (Uysal et al, 2017).…”
Section: Jumlah Bal Pada Feses Dan Isi Sekum Mencitunclassified
“…Our study also showed that rats receiving a misinjection of PB take longer to achieve LORR. Unfortunately, it appears that misinjections are always possible, in part due to the variable location of the cecum [7,18,19,29,30].…”
Section: Rgsmentioning
confidence: 99%
“…This study only used one dose of PB. This dose was selected from previous work demonstrating benefits in terms of a faster death and reduced variability of effects [ 7 , 18 , 19 , 29 ]. The occurrence of misinjections appears to be an inherent drawback of IP injections, leading to the ongoing search for alternative injectable euthanasia methods [ 31 – 33 ].…”
Section: Limitations and Future Studiesmentioning
confidence: 99%